2016
DOI: 10.1002/2016jd024789
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic field changes and durations of narrow bipolar events

Abstract: Using an array of 10 sensors, electric field change measurements of 35 positive narrow bipolar events (NBEs) were obtained at close range (≤10 km). At the closest sensor all 35 NBEs had a net electrostatic change (ΔEfast) associated with the main bipolar pulse with amplitudes of 0.4 to 16.3 V/m (not range normalized). At the closest sensor the bipolar pulse of each of the 35 NBEs was followed by a relatively long, slow electrostatic change (ΔEslow) with amplitudes of 0.1 to 43.4 V/m and durations of 0.7 to 33.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 30 publications
3
15
0
Order By: Relevance
“…Note that the static field has a polarity opposite to that of the initial radiation field. This feature is in agreement with the experimental data presented in [39] and [40].…”
Section: Field Signature As a Function Of The Distancesupporting
confidence: 93%
See 1 more Smart Citation
“…Note that the static field has a polarity opposite to that of the initial radiation field. This feature is in agreement with the experimental data presented in [39] and [40].…”
Section: Field Signature As a Function Of The Distancesupporting
confidence: 93%
“…So far, we have studied the effect of various parameters of the streamer burst on the radiation field generated by CIDs. Not much information is available on the field signatures of CIDs measured close to their point of origin, but references [39] and [40] provide a few examples. These examples show the presence of a static field in the close signature of the NBP.…”
Section: Field Signature As a Function Of The Distancementioning
confidence: 99%
“…[] determined the average charge moment of 15 positive NBEs to be 380 C m with a range of 260–800 C m, and Karunarathne et al . [] found that the average charge moment of 10 positive NBEs measured within the reversal distance was 1090 C m with a range of 460–1810 C m. Rison et al . [] calculated the charge moments of three NBEs that initiated IC flashes and found them to be −80, −90, and −180 C m. Thus, the largest charge moments of FPBs that initiate IC flashes (namely, NBEs) can be substantially larger than the largest IEC charge moments measured herein.…”
Section: Are Iecs a Fundamental Needed Part Of Lightning Initiation?mentioning
confidence: 92%
“…[, Figures 2 and 3], and Karunarathne et al . []. Therefore, we identify the two IEC initiating pulses in Figure as NBE‐type pulses.…”
Section: Iecs Nbes and Lightning Initiationmentioning
confidence: 99%
See 1 more Smart Citation